Analysis of the Influence of Customer Orientation on Sales Performance Through Value-Based Selling as a Moderating Variable - Christian Jordan Santoso; M. Sigit Taruna; Dian Milasari (Business, Accounting, and Knowledge Journal, 2025)
ABSTRAK This study examines how customer orientation influences sales performance, with value-based selling acting as a moderating variable for Vespa Motor sales personnel at BCA Multifinance Pekalongan. The type of research used in this study is correlational research with data collection methods using questionnaires. This study utilized a sample of 110 respondents. The sampling method used was purposive sampling. The analytical tool used is moderation regression analysis. The analysis results indicate that customer orientation has a negligible negative impact on sales performance. Value-based selling has an insignificant positive effect on sales performance. Value-based selling can strengthen the relationship between customer orientation and sales performance. This research aims to provide a more comprehensive understanding of value-based selling strategies that respond to the continuously evolving dynamics of consumer behavior. Theoretically, this research is also expected to enrich the literature in the field of marketing, particularly in the context of the automotive industry and vehicle financing.